Intravenous Ondansetron Efficacy in Preventing Post Spinal Shivering during Lower Segment Caesarean Section - Abid, Komail; Iqbal, Rashid; Shah, Syed Ali Raza; Tariq, Sana (Pakistan Armed Forces Medical Journal, 2023)
Objective: To determine IV Ondansetron efficacy in preventing post-spinal shivering during LSCS. Study Design: Quasi-experimental study. Place and Duration of Study: Department of Anaesthesiology, Combined Military Hospital, Rawalpindi Pakistan, from Sep 2018 to Mar 2019. Methodology: A total of 60 women undergoing LSCS under spinal anaesthesia were included. Group-A was given 8 mg/4 ml Ondansetron, while Group-B was given 4 ml Normal Saline 0.9% IV immediately before induction of spinal anaesthesia. Body temperature, level of sensory block, and shivering scores during the peri-operative period were recorded. After surgery, patients were shifted to Post Anaesthesia Care Unit (PACU). Shivering was graded using Crossley and Mahajan 5-item scale. Injection Tramadol 1mg/kg intravenously was used as a rescue anti-shivering drug. Results: The majority of the patients 33(55.0%) were between 18-25 years of age. Efficacy of Intravenous Ondansetron in preventing post-operative shivering during spinal anaesthesia in patients undergoing caesarean section was seen in 26 86(67%) patients (Group-A) as compared to 17(56.67%) patients in the Control Group (Group-B) (p-value=0.010). Conclusion: The study concluded that there was less post-operative shivering with intravenous Ondansetron during spinal anaesthesia in patients undergoing caesarean section as compared to the Control Group.